Sistem Informasi Adminitrasi Santri Pondok Pesantren Al-Fadlu Wal Fadilah Kaliwungu dengan Metode Agile Berbasis Web - Pramesty, Nazhwa Resta; Sugiyamta, S (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Technological progress is progressing very rapidly. Almost all activities use information technology to achieve maximum results. In educational institutions, the presence of information systems to increase efficiency and effectiveness is very important. So far, the management of the Al Fadl Wal Fadillah Kaliwungu Islamic Boarding School is still manual. The weakness is that the data is inaccurate, the data is difficult to find, and the process is very time consuming and slow. Therefore, Pondok Pesantren Al-Fadlu wal Fadilah Kaliwungu needs a web-based santri administration information system, which provides solutions so that santri parents do not have to make direct payments to come to the lodge but make payments through the available web and can do so effectively and efficiently. This system using the Agile method from this study resulted in the administration system of Pondok Pesantren Al Fadl Wal Fadillah Kaliwungu to make it easier for users to access this system and run according to the needs of Pondok Pesantren Al Fadl Wal Fadillah Kaliwungu.